A comment on "Sequential Equilibria" - Peter A. Streufert (The University of Western Ontario, Department of Economics, 2006)
[Introduction] In addition to introducing the path-breaking concept of sequential equilibrium, Kreps and Wilson (1982) (henceforth KW) contains three insightful theorems which derive the geometry of the set of sequential equilibrium assessments, the finiteness of the set of sequential equilibrium outcomes, and the perfection of strict sequential equilibria. These derivations depend upon Lemmas A1 and A2 in the KW appendix. Section 3 of this paper notes that the KW proofs of these lemmas contain a nontrivial fallacy. Section 4 repairs these proofs by means of Streufert (2006b).
Keywords: 330